THE ROLE OF APOPTOSIS AND AUTOPHAGY IN BOVINE ABORTIONS ASSOCIATED WITH BRUCELLA SPP - Ozkaraca, Mustafa; Ceribasi, Songul; Ceribasi, Ali Osman; Kilic, Ayse; Ongor, Hasan (Sciendo, 2016)
This study is aimed to evaluate the relationship between the severity of apoptotic and autophagic cell death based on the distribution of Brucella spp. antigens in the lung, liver, kidney, spleen, brain, heart, skeletal muscle, mesenteric lymph node, and thymus tissue from bovine fetuses aborted due to natural infection with Brucella spp. The distribution of Brucella spp. antigens was immunohistochemically examined in the tissues of 16 aborted fetuses from cattle diagnosed with Brucella spp. infection by a polymerase chain reaction (PCR). In addition, immunostaining of primary antibodies for cleaved caspase 3 was performed to detect apoptosis, and immunostaining of Microtubule Associated Protein 1 Light Chain 3 Beta (LC3B) was used to detect autophagy in the Brucella spp.-related abortions. Analysis of cellular death revealed strong immunopositivity in the lung, spleen, kidney, and thymus, moderate immunopositivity in the liver, mesenterial lymph nodes, and heart muscle and slight immunopositivity in the brain and skeletal muscle by staining of Brucellaspp. antigens. According to the immunohistochemical results, the immunopositivity of cleaved caspase 3 and LC3B was extremely high in the lung, thymus, spleen, kidney, and liver tissues. The immunostaining of cleaved caspase 3 in the lung, thymus, and kidney tissues was severe compared to that of LC3B. In the liver, spleen, and mesenterial lymph nodes, the immunopositivity of LC3B was higher than that of cleaved caspase 3. Bacterial antigens were highly evident in the lung, spleen, kidney, and thymus tissues of Brucella spp.-related bovine abortions, and both apoptosis and autophagy played a role in cellular death.
Keywords: Brucella spp.; cleaved caspase 3; immunohistochemistry; LC3B